Comparison of Audiovisual Components of Dance in Novices and Experts' Aesthetic Interest Perceptions. (July 2023) - Joung, Jeehyun; Kim, Jeounghoon
Aesthetic appreciation of dance is associated with external components of physical features and audiences' subjective aspects, which can be explained by cross-modal integration. In this study, we designed aesthetic appraisal tasks measured on a 5-point Likert scale by manipulating audiovisual combinations of dance movements and musical properties to measure novices and experts' interest appraisals. Using statistical analyses and psychometric curve fitting, we found that novices judged that variations in travel patterns on stage and moving the entire body were interesting. In contrast, experts judged that the variation in the dancer's upper body parts synchronized only with the time signature was interesting. Accordingly, while novices had a low interest decision threshold for dancing across the stage and a high range of body configurations, experts had a high threshold for those cases. Overall, only experts had the ability to integrate audiovisual contents to appreciate the aesthetic values in dance movements.